Implantable vaginal drug delivery system of zidovudine for site specific activity (Asian Journal of Pharmaceutics (AJP), 2014)
The present work aims at the formulation of novel antiâ€human immunodeficiency virus vaginal compactable inserts to enhance the pharmacological effects of zidovudine (AZT). Attempt was taken to design a dosage form, which providessustained release of the drug at the site of action so as to minimize the overall dose and dosing frequency that can reduce the risk of sideâ€effects. Different formulations of the vaginal compacts of AZT were prepared employing wet granulation method, utilizing several mucoadhesive polymers such as hydroxypropyl methyl cellulose (HPMC 5, 15, 50, 3000 cps) and methylcellulose (MC) at 20%, 30% and 40% concentrations. The formulations were evaluated and postâ€compression parameters including drug content, swelling study, in vitro diffusion, dissolution and drug release kinetic studies. Instrumental analysis like differential scanning calorimetry as well as Fourier transform infrared spectroscopy were performed to find the change in thermal properties and the possible interactions between drugâ€polymer, respectively. Xâ€ray diffraction study was also done to reveal the modification of crystalline nature of drug in the formulation. The compacts prepared by HPMC 50 cps (40%) exhibited the better results in terms of swelling with sustained drug release through the gelled layer. Regardless of good physicochemical parameters, MC did not display a good polymer of choice due to accumulation of spongy gelled blanket around the compact, which is not homogenous but stiff and brittle.